Finding your ethical research self : a guidebook for novice qualitative researchers - Tolich, Martin (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Finding Your Ethical Research Self introduces novice researchers to the need for ethical reflection in practice and gives them the confidence to use their knowledge and skill when, later as researchers they are confronted by big ethical moments in the field. The 12 chapters build on each other, but not in a linear way. Core ethical concepts like consent and confidentiality once established in the early chapters are later challenged. With numerous examples of ethical dilemmas and issues and questions and exercises to encourage self-reflection, this reflexive, learn-by-doing model of research ethics will be highly useful to the novice, undergraduate and postgraduate research student"--
OCLC-licensed vendor bibliographic record.
Keywords: Qualitative research -- Moral and ethical aspects; Social sciences -- Research -- Moral and ethical aspects; SOCIAL SCIENCE / Research